Emergence of New Delhi metallo-beta-lactamase 1 and other carbapenemase-producing Acinetobacter calcoaceticus-baumannii complex among patients in hospitals in Ha Noi, Viet Nam. - Tran, D; Tran, H; Matsui, M; Suzuki, M; Suzuki, S; Shibayama, K; Pham, T; Van Phuong, T; Dang, D; Trinh, H; Loan, C; Nga, L; et al. (Springer, 2016)
Acinetobacter baumannii is an important cause of multidrug-resistant hospital acquired infections in the world. Here, we investigate the presence of NDM-1 and other carbapenemases among carbapenem-resistant A. baumannii isolated between August 2010 and December 2014 from three large hospitals in Hanoi, Vietnam. We identified 23/582 isolates (4 %) (11 from hospital A, five from hospital B, and seven from hospital C) that were NDM-1 positive, and among them 18 carried additional carbapenemase genes, including seven isolates carrying NDM-1, IMP-1, and OXA-58 with high MICs for carbapenems. Genotyping indicated that NDM-1 carrying A. baumannii have expanded clonally in these hospitals. Five new STs (ST1135, ST1136, ST1137, ST1138, and ST1139) were identified. One isolate carried NDM-1 on a plasmid belonging to the N-repA replicon type; no NDM-1-positive plasmids were identified in the other isolates. We have shown the extent of the carbapenem resistance and the local clonal spread of A. baumannii carrying NDM-1 in these hospitals; coexistence of NDM-1 and IMP-1 is reported for the first time from Vietnam here, and this will further seriously limit future therapeutic options.